2019
DOI: 10.1167/iovs.19-26626
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Activated Chloride Channels in Newly Differentiating Mouse Lens Fiber Cells and Their Role in Volume Regulation

Abstract: PurposeChloride channels have been proposed to play an important role in the regulation of lens volume. Unfortunately, little information is available about the molecular identity of these channels or how they are regulated in the lens due to the difficulties in isolating mouse fiber cells. Recently, our laboratory has developed a new technique for isolating these cells by using transgenic mouse lenses that lack both Cx50 and Cx46. The purpose of this study was to test the hypothesis that newly differentiating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…In conclusion, this study describes the effect of two potent modulators of the TRPV4 channels on the CaCCs, specifically on cloned TMEM16B and further experiments are required to understand the T out current enhancement in oocytes. Our findings suggest careful interpretations of pharmacological studies performed on tissues where TRPV4 and TMEM16B channels co-express [ 55 ] and helps to achieve precise conclusions in preclinical studies about TRPV4. Finally, our observations indicate that the GSKa/b structures may be used as templates to design new potent and selective drugs for TMEM16B.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In conclusion, this study describes the effect of two potent modulators of the TRPV4 channels on the CaCCs, specifically on cloned TMEM16B and further experiments are required to understand the T out current enhancement in oocytes. Our findings suggest careful interpretations of pharmacological studies performed on tissues where TRPV4 and TMEM16B channels co-express [ 55 ] and helps to achieve precise conclusions in preclinical studies about TRPV4. Finally, our observations indicate that the GSKa/b structures may be used as templates to design new potent and selective drugs for TMEM16B.…”
Section: Discussionmentioning
confidence: 93%
“…Physical and functional coupling between CaCCs with TRPVs have been already demonstrated in heterologous expression and in tissues [ 43 , 44 , 52 ]. Studies to elucidate the possible pharmacological interaction of both channel families are essential to generate accurate conclusions, especially in tissues where both channels are expressed like in DRG, choroid plexus epithelial cells and retinal epithelium [ 26 , 44 , 45 , [53] , [54] , [55] ].…”
Section: Discussionmentioning
confidence: 99%
“…In shorter fiber cells from the zone of chloride efflux, this chloride current was generally quiescent but could be activated by hypotonic challenge and/or addition of the KCC blocker, DIOA. More recently, we have shown that calcium-activated-chloride channels (CaCCs) composed of TMEM16A and TMEM16B were expressed in newly differentiating lens epithelial and fiber cells in wild-type and double knockout (KO) that lack both Cx50 and Cx46 using a combination of reverse transcript PCR (RT-PCR), immunohistochemistry and whole cell patch clamp techniques (Tong et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…One of the main advantages of using this preparation to perform electrophysiological experiments is that the isolation of fiber cells from lens of these KO mice can be performed using milder dissociation conditions than those used in past attempts to dissociate fiber cells, possibly due to alterations in cell adhesion properties (Wang et al, 2016;Hu et al, 2017). Another advantage is that the double KO fiber cells lack large, calcium-sensitive connexin hemichannel currents and can tolerate exposure to calcium-containing solutions without requiring the addition of non-specific cation channel blockers such as 1 mM Gadolinium to prevent fiber cell vesiculation and death (Ebihara et al, 2011;Tong et al, 2019). Our results demonstrate that CaCCs in dissociated lens can be rapidly and reversibly modulated by mechanical stress, consistent with their participation in regulation of volume in this organ.…”
Section: Introductionmentioning
confidence: 99%
“…They express large amounts of crystallins in the cytosol, they lose Na/K ATPase activity in the membranes, 8 and the abundance of potassium channels diminishes while expression of sodium and chloride leak channels increases. [9][10][11] These fibers are coupled by gap junctions made from Cx50 and Cx46. 12 Their coupling conductance is concentrated in the equatorial region.…”
mentioning
confidence: 99%